Genetic Parameters of Some Characters and Their Correlation with Rice Grain Yield in Relation to the Plant Adaptability to Semi-Deep Stagnant Flooding Condition - Nugraha, Yudhistira; Vergara, Geogiana V.; Mackill, David J.; Ismail, Abdel Bagi (Pusat Penelitian dan Pengembangan Tanaman Pangan, 2013)
Stagnant flooding (SF) is a major problem in floodprone rice ecosystem where the depth of flood water ranging from 20-50 cm in the entire seasons. In Indonesia this kind of water stress can be found in swampy basin area or Rawa Lebak. A study was conducted to determine the genetic parameters related to rice plant adaptability to SF. Eighteen rice genotypes including the recently developed 6 pairs of SUB1 near isogenic lines (NILs) of widely planted varieties and checks were tested under 50 cm depth of SF in the 2009 wet season at Los Banos, Philippines. The results showed that most of genotypes showed different responses on morphological and agronomical characters under SF and normal conditions. Most of the SUB1 NILs had lower grain yields than their respective parents. This was because SUB1 suppressed shoot elongation and less restoring contact with the air. Some SUB1 lines such as PSBRc68 and IR70181-32, however, produced high grain yields under this condition. Under SF condition, rice genotypes required shoot elongation to allow restoring contact with the air, therefore the traits that related to growth attributes such as shoot weight, leaf weight, LAI, stem diameter, plant high, and tiller number were strongly correlated with the grain yields. These traits also had broad genetic variability, high heritability, and strong correlation with grain yields. Selection under real stress SF conditions was effective to obtain high yielding genotypes and also tolerant.